2023
DOI: 10.3390/ijerph20075385
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of High-Resource Health System Users in Rural and Remote Regions: A Scoping Review

Abstract: A small proportion of health care users are recognized to use a significantly higher proportion of health system resources, largely due to systemic, inequitable access and disproportionate health burdens. These high-resource health system users are routinely characterized as older, with multiple comorbidities, and reduced access to adequate health care. Geographic trends also emerge, with more rural and isolated regions demonstrating higher rates of high-resource use than others. Despite known geographical dis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Widespread rural barriers to healthcare, due to factors such as lack of medical practitioners and transportation problems, could worsen stigma-related health disparities among those who identify as a sexual minority; however, the evidence base is mixed, as LGB persons living in rural areas may also be more likely to report a greater sense of belonging than their urban peers [35]. Much of the existing literature on rural-urban differences in health outcomes is singularly limited to geographic barriers to healthcare access [26]; our analysis highlighted rural heterogeneity in access across socially marginalized groups. Results showed that LGB persons more often exhibited behaviors associated with chronic stress, including tobacco smoking and regular alcohol consumption, compared with heterosexual persons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Widespread rural barriers to healthcare, due to factors such as lack of medical practitioners and transportation problems, could worsen stigma-related health disparities among those who identify as a sexual minority; however, the evidence base is mixed, as LGB persons living in rural areas may also be more likely to report a greater sense of belonging than their urban peers [35]. Much of the existing literature on rural-urban differences in health outcomes is singularly limited to geographic barriers to healthcare access [26]; our analysis highlighted rural heterogeneity in access across socially marginalized groups. Results showed that LGB persons more often exhibited behaviors associated with chronic stress, including tobacco smoking and regular alcohol consumption, compared with heterosexual persons.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not find a significant association between degree of residential remoteness and hospitalization risk among those with an underlying cardiometabolic condition, statistical power was reduced when limiting the analysis to a small subgroup and for a relatively rare outcome. Moreover, the analysis was conducted for Canada, a high-income country characterized by universal healthcare coverage, considerable legal protections with regard to sexual minority populations [39], and a vast sparsely populated rural geography [26]. In countries with mixed healthcare payment systems, insurance status has been found to contribute significantly to health disparities among sexual minority groups, notably in the United States where the uninsured are numerous [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation